Building a common description of land cover in a tropical watershed plagued with intercultural conflicts: The value of participatory 3D modelling - Mathieu Guillemette; Catherine Potvin; Lauliano Martinez; Bonarge Pacheco; Dioniz Caño; Ignacio Pérez (Canadian Science Publishing, 2017)
Natural forest management and conservation projects such as reducing emissions from deforestation and forest degradation, and enhancing forest carbon stocks (REDD+) face many challenges in the field. Implementation of these projects depends on such factors as clarity of information among stakeholders, legal security of territories, and local decision-making power. These challenges have been previously identified in the Upper Bayano watershed of eastern Panama, where a long history of land cover and land-use conflicts is present between three different human groups. With a long-term objective of natural forest conservation, this study aims to develop and test participatory approaches (participatory mapping and participatory 3D modelling) for the Upper Bayano watershed in an attempt to create a consensus among all stakeholders on current land cover and land-use conflicts to overcome challenges faced by projects as REDD+. We found that the third dimension allows a common understanding over the landscape, creates a common ground discussion, and leads towards a consensus, while the participatory approach brings discussion and positive effects among the stakeholders and the bridging institutions bring equity and transparency. Finally, we discuss implications of this knowledge generation and common agreement over the landscape for future forest management projects such as REDD+'s implementation.